POLITIK ORGANISASI INTERNASIONAL : KEPENTINGAN AMERIKA SERIKAT MELALUI UNHCR DALAM PEMBERIAN REFUGEE STATUS DETERMINATION DI RUMAH DETENSI IMIGRASI PUSAT TANJUNGPINANG - Saragih, Jecklin; Susetianingsih, Hermini; Rosyidin, Mohamad (Journal of International Relations, 2015)
Immigrant become an important issue because some state used it for atool to fight for their interest. Tanjungpinang UNHCR discriminativepolicy for the sake of the interest of the donor state resulted a loss inUNHCR independency in giving a humanitarian aid. This researchobjective is to know United States through UNHCR within RefugeeStatus Determination giving in Rumah Detensi Imigrasi PusatTanjungpinang. In knowing that interest, used a theory called realismtheory. The type of this research is mixed methods that analyzed theTanjungpinang UNHCR discriminative policy that favor theAfghanistan nationality immigrant in Rumah Detensi Imigrasi PusatTanjungpinang. The discriminative policy that occur is to favor anAfghanistan nationality immigrants in term of giving the refugeestatus determination. The obtained result by this research shows thatUNHCR discriminative policy are not to bring United States interestto reform their image, but more to fight for their other interest.